Overweight/obesity, body composition and bone mass in late adolescence: the relation with birth weight, childhood body mass index and growth. The Tromsø Study: Fit Futures, a longitudinal cohort study - Evensen, Elin Kristin (Pediatric Obesity, 2019)
Background and aim : High prevalence of childhood overweight/obesity is a major health concern due to related immediate and long-term health problems. Early identification of children at risk is of interest, as preventing or delaying the onset of obesity may influence future health. The aim of this thesis was to study how early life factors such as birth weight, childhood body mass index (BMI, kg/m2) and growth are related to overweight/obesity, body composition and bone health in adolescence. Methods : The Tromsø Study, Fit Futures (TFF) is a population-based cohort study with participants from Tromsø and neighbouring municipalities. Two waves were conducted in 2010-2011 (TFF1) and 2012-2013 (TFF2). Data from a representative sample of 961 adolescents (48% girls) from TFF1, of which 659 had follow-up data from TFF2, formed the basis for this thesis. Longitudinal anthropometric data were retrospectively obtained from the Medical Birth Registry of Norway and childhood health records at 2-4 and 5-7 years. Body composition (fat mass and fat-free mass) and bone mass and bone density were measured by dual-energy X-ray absorptiometry at 15-17 and 18-20 years of age. In addition, height, weight and waist circumference was obtained. Participants were classified into BMI categories: underweight, normal weight, overweight and obese, according to the International Obesity Task Force age- and sex-specific cut-off values for children 2-18 years of age. Results : The prevalence of overweight including obesity increased with age and 21% of girls and 28% of boys were overweight/obese at 18-20 years of age. There was a modest association between birth weight and overweight/obesity at 15-20 years of age, and birth weight was significantly associated with higher fat-free mass as well as bone mass in adolescence. The degree of tracking of BMI from 2-4 and 5-7 years of age up to 15-20 years of age was moderate, with stronger associations observed for more severe overweight and obesity. Overweight/obesity at 6.0 and 16.5 years of age ...